Perspectives on agriculturally used drained peat soils: Comparison of the socioeconomic and ecological business environments of six European regions. (January 2020) - Buschmann, Christoph; Röder, Norbert; Berglund, Kerstin; Berglund, Örjan; Lærke, Poul Erik; Maddison, Martin; Mander, Ülo; Myllys, Merja; Osterburg, Bernhard; van den Akker, Jan J.H.
Highlights: Economic variables determine alternatives to conventional agricultural peatland use. System productivity, economic value of land and market incentives are decisive. Heterogeneity of users and conflicts are important for alternative implementation. Mainly EU-level incentives are necessary for financing alternative land use. They must be accompanied by institutional changes at EU, national and regional levels. Abstract: In Northern, Eastern and Central European countries, peat soils drained for agriculture are a considerable source of greenhouse gas emissions. Since emissions from this source have high mitigation potential, they will likely be a focus of the European Union's future climate goals. We describe and compare the similarities and differences in the socioeconomic and ecological business environment that policy makers, planners and farmers are confronted with when developing tailored proposals for low emission land use alternatives on peat land. The analysis is based on interviews with 33 typical farmers cultivating organic soils and on expert group discussions held in six different Northern, Eastern and Central European regions. Based on the Social-Ecological System Framework we identify and cluster important variables. Our results show that mainly hard economic variables determine preferred land use alternatives: the productivity of resource systems, the economic value of land and market incentives. Other variables, such as the heterogeneity of users and conflicts among them, are more important with respect to the implementation of alternatives. We point out possibilities to transfer solutions between regions and discuss an institutional framework for European Union, national and regional levels for facilitating implementation potential.